ANALYSIS OF THE ENTREPRENEUR SPIRIT OF THE KATEGE COFFE SHOP BUSINESS IN TARGETTING MILLENNIALS IN JEMBER - Putri, Tika Yulia Sari; Setianingsih, Wahyu Eko; Rahayu, Jekti (Universitas Muhammadiyah Tangerang, 2024)
In this research, the problem that occurs is how the Entrepreneur Spirit of the owner of KATEGE Coffee Shop to target millennials in the Jember Regency area. Entrepreneur is the ability to create value for business development. Spirit Entrepreneur arises because of changes in lifestyle along with the times, especially the millennial generation which is synonymous with new things and digitalization. The purpose of this research is to explain the entrepreneurial spirit of KATEGE coffee shop owners in attracting millennial generation targets. Qualitative methods are used in this research directly by observing the object under study and conducting interviews. As for data analysis using Milles and Hubberman analysis. The results showed that the entrepreneurial spirit possessed by the coffee shop owner through a proactive attitude.